The Washington manual general internal medicine subspecialty consult. - Cislo, Geoffrey S.; De Fer, Thomas M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
"Prepared by residents, fellows, and attending physicians, this handbook is a practical guide to the general internal medicine consult. The content is based on the top 25 most common general internal medicine consults as seen by the hospitalist. The focus is on management issues, with additional material on the perioperative care of the patient with a medical condition. Clinical evidence is presented along with the official guidelines advocated by major medical organizations." "This Second Edition is completely revised and updated. Illustrations have been added, and key points about diagnosis and management have been bulleted for easy reference."--BOOK JACKET.
Includes bibliographical references and index.
committed to retain
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Internal medicine -- Handbooks, manuals, etc; Internal Medicine -- methods -- Handbooks; Electronic books